The Intervening role of Absorptive Capacity in the Nexus of Effectual Actions and Performance in Small Businesses - Osuigwe, Ubochioma Udo S; Eresia-Eke, Chukuakadibia (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: This study interrogates the interfering role of absorptive capacity in the relationship between the effectual actions of small businesses and their performance. Design/methodology/approach: Structured questionnaires were used to generate primary data from 685 small businesses from a variety of sectors in South Africa. The data was used to interrogate the hypothesized relationships using the partial least squares structural equation modeling technique. Findings: The findings report a significantly positive relationship between effectuation and small business performance. Further, it is revealed that absorptive capacity partially mediates the relationship between effectuation and small business performance. Research limitations/implications: The limitations of this study include the use of primary data from a sample of small businesses in South Africa and dependence on specific modeling techniques. The implications of this research provide a deeper understanding of the mediating effects of absorptive capacity on the relationship between effectual actions and small business performance. Practical implications: This study provides fresh insights into the mediating effects of the absorptive capacity capability of small businesses in the continuous interaction between their effectual actions and performance. As such, it highlights the connection between the growing theory of effectuation and existing theories in the field of management sciences. This study enables the emergence of knowledge that could spur small businesses to effectively navigate the endemic uncertainties prevalent in their contexts. Originality/value: This study contributes to the understanding of the role of absorptive capacity in the relationship between effectual actions and small business performance, thus adding value to the literature on small business management. Paper type: This research is empirical.